Antimigratory and antimetastatic effect of heparin-derived 4–18 unit oligosaccharides in a preclinical human melanoma metastasis model - Kenessey, István; Simon, Erika; Futosi, Krisztina; Bereczky, Bíborka; Kiss, Andrea; Erdödi, Ferenc; Gallagher, John T.; Tímár, József; Tóvári, József (Thrombosis and Haemostasis, 2009)
Heparin and its derivatives have been shown to inhibit angiogenesis and metastasis formation. Accordingly, we investigated the effect of heparin fragments containing 4 to 22 monomers on human melanoma cell proliferation, migration and invasion in vitro as well as on the in vivo metastatic potential in a SCID mouse model. Only oligosaccharide dp18 had significant inhibitory effect on cell proliferation. In contrast, cell migration was inhibited by all oligosaccharides studied except dp8 and dp22. Anti CD44v3 antibody stimulated cell migration and invasion, and this effect could be attenuated by oligosaccharides dp4 and dp18. These fragments also inhibited the catalytic activity of myosin light chain phosphatase as well. Moreover, oligosaccharides dp4 and dp18 reduced the number of lung colonies formed in SCID mice intravenously injected with human melanoma cells, while dp22 proved to be ineffective in this respect.These studies revealed that fragments of heparin have an antimigratory and antimetastatic potential. These fragments lack the haemostatic effect of heparin, suggesting that they are potential specific antimetastatic agents in anticancer therapy.
Keywords: Melanoma; oligosaccharides; cell; migration; xenograft; metastasis model